KINETICS OF SORPTION OF Pb (II) IONS FROM ARTIFICIAL SOLUTIONS ON NATURAL POLYMERS (Scientific journal of the Fergana State University, 2022)
In this work, we studied the sorption kinetics of lead (II) ions from artificial solutions on hair fibers, which are biological waste polymers. In this case, the kinetics were studied using pseudo-first and second-order kinetic models, and the results showed that the uptake of Pb (II) ions in activated hair fibers follows a pseudo-second order kinetic model. The maximum adsorption capacity of lead was 76.125 mg/g. The isothermal models of Langmuir and Freundliсh were used to represent the mechanism of adsorption at equilibrium. Based on the results obtained, it was found that the values ​​of the calculated isotherm parameters (R2=0.9333 and R2=0.9281) correspond to all isotherm models. The value of the Freundlich parameter is n=2.74, which indicates a high sorption. According to the Langmuir equation, the correlation coefficient R2 for Pb(II) ions is 0.9333, and the change in concentration indicates that the adsorption process obeys the Langmuir theory of monomolecular adsorption (RL). This indicates the sorption of Pb(II) ions by activated hair fibers.